Common Enterobacterial Antigen III. Initial Titers and Antibody Response in Bacteremia Caused by Gram-Negative Bacilli - McCabe, William R. (1973)
Antibody titers to common enterobacterial antigen (CA) were determined in 141 controls and in acute serum specimens from 206 patients with bacteremia caused by gram-negative organisms. Levels of antibody to CA ranged from 1:160 to 1:2,560 in 95% of control subjects. These levels did not differ significantly from those in acute serum specimens from bacteremic patients with “nonfatal underlying diseases.” Patients with more severe underlying diseases, “ultimately fatal underlying diseases,” tended to have lower titers of antibody to CA. Human antibody to CA was predominantly of the 19S variety. A fourfold change in antibody titer to CA was observed in convalescent serum obtained after bacteremia in 32% of 108 patients studied. Correlation of titers of antibody to CA in acute serum specimens with the frequency of occurrence of shock or death failed to demonstrate any protective activity of antibody to CA. These complications occurred equally as often in patients with high titers of antibody to CA as in those with low titers.